Aplikasi Penyembunyian Data Rahasia Ke Citra Digital dengan menggunakan Metode Rivest Shamir Adleman dan Least Significant Bit - Zalukhu, Feliso (LPPM UNIKA Santo Thomas Medan, 2018)
Steganography is the science of art and science to make hidden messages in a certain way so that other people besides the sender and recipient will realize there is a hidden message. Cryptography is science and art to learn about processing and securing messages safely. This study will discuss the combination of the Rivest Shamir Adleman (RSA) and Least Significant Bit (LSB) methods on how to hide a secret message in a digital image. A text message before being inserted into a digital image is first encrypted with the RSA Algorithm, the results of the encryption are inserted digital imagery with LSB Algorithm. The length of the text message depends on the size of the container media. Applications designed using Microsoft Visual Basic 2008 also provide interfaces for generating randomly needed keys. Applications can be used to hide secret messages in digital images where the color changes of input images with results are not clearly visible.